2012
DOI: 10.1017/s1368980012002868
|View full text |Cite
|
Sign up to set email alerts
|

Sources of weaning advice, comparisons between formal and informal advice, and associations with weaning timing in a survey of UK first-time mothers

Abstract: Objective: The aim of the present study was to explore knowledge of the UK weaning guidelines and the sources of weaning advice used by UK first-time mothers. Design: An online survey of UK parents; analysed using mixed methods. Setting: Participants were recruited from a selection of parenting websites that hosted a link to the survey. Subjects: In total, 1348 UK first-time mothers were included in the analysis. Results: Knowledge of the guidelines was high (86 %) and associated with later weaning (P , 0?001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 14 publications
1
29
1
Order By: Relevance
“…2011a; Moore et al . ). Younger mothers are more likely to listen to the advice of family and friends when it comes to infant care (Brown et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2011a; Moore et al . ). Younger mothers are more likely to listen to the advice of family and friends when it comes to infant care (Brown et al .…”
Section: Discussionmentioning
confidence: 97%
“…Moore et al . 2012a,b). The findings have important implications for those supporting new mothers, to understand the factors that drive decisions at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Text-mining has been used previously to process large amounts of online data from social networks 14–17. A simpler type of text-mining (keyword-in-context analysis) has also been used in online and media portrayals of heath topics18–20 and small scale surveys 21. The Information Strategy for NHS England encourages analysis of data from patients 22.…”
Section: Introductionmentioning
confidence: 99%
“…The last UK-wide infant feeding survey showed that mothers whose own mothers used formula milk are less likely to breastfeed (McAndrew et al, 2012). Furthermore, mothers who introduced solid foods before 17 weeks have been found to be predominantly influenced by advice from their own mother or grandmother (Moore et al, 2012), a historical advice context that provides the formative experience for grandparents who go on to support subsequent generations of mothers.…”
Section: Introductionmentioning
confidence: 99%